Nexus Between Agriculture, Industrialization, Imports, and Carbon Emissions in Bangladesh - Rahman, Md. Shoaibur; Ridwan, Mohammad; Raihan, Asif; Khayruzzaman; Tanchangya, Tipon; Rahman, Junaid; Foisal, Md. Zia Uddin; Mohajan, Babla; Rafi, Azizul Hakim; Islam, Samanta; Paul, Arindrajit (Journal of Environmental and Energy Economics, 2023)
Global warming is a significant worldwide challenge, principally caused by the ongoing increase in carbon dioxide (CO2) concentrations. Confronting this dilemma necessitates inventive solutions and anticipatory actions to alleviate the consequences. This paper analyzes the influence of Bangladesh’s agriculture, industrialization, and imports on CO2 emissions to inform sustainable development strategies. The dynamic ordinary least squares (DOLS) method was applied by utilizing time-series data from 1971 to 2023. The unit root tests were used to ensure the data stationarity. The results of the DOLS estimation revealed that a 1% increment in the agricultural value added would reduce CO2 pollution by 0.51% in the long run. However, a 1% increase in industrialization and imports causes higher carbon emissions in Bangladesh by 1.39% and 0.64%, respectively. The research highlights the significance of advancing green manufacturing methods, improving agricultural efficacy, and limiting imports as crucial gauges for reducing CO2 emissions and attaining ecological longevity in Bangladesh.